ETNOLINGUISTIC ANALYSIS OF TRADITION RELATED LEXICON IN THE KARAKALPAK AND ENGLISH LANGUAGES - Baxieva, Mexriban Tlewbergenovna (SCIENCE and SOCIETY, 2026)
The article compares harvest and festival vocabulary in Karakalpak and English. Karakalpak focuses on Zuraat Bayram (cotton harvest, community, Islamic-nomadic roots). English shows Carnival (indulgence) and Halloween (supernatural). Similarities exist in harvest themes; big differences in religious and ritual meaning. Language preserves cultural identity.
Keywords: ethnolinguistic; lexicon; festivals; beliefs; traditions; English language; Karakalpak language; harvest; cultural comparison